Apathy in subarachnoid hemorrhage: study protocol for a 1-year follow-up study - Tang, Wai Kwong; Wong, Kwok Chu George (Frontiers in Neurology, 2024)
Introduction: Apathy is a frequent and debilitating condition among subarachnoid hemorrhage (SAH) survivors. Few studies have evaluated apathy in SAH, and none have examined the course of the condition, predictors of persistent apathy, or its impact on functional outcomes. The proposed study will examine, for the first time, the 12-month course of apathy and its impact on functional outcomes in the largest cohort of SAH survivors to date.The current study is designed as a prospective cohort study with a duration of 36 months. We will recruit 240 participants. A trained research assistant will assess apathy using the Apathy Evaluation Scale 3 months after SAH. Patients' level of functioning, comorbidity, global cognitive functioning, and depressive symptoms will be assessed. All SAH patients will participate in follow-up assessments of apathy and functioning at 9 (T2) and 15 months (T3) post-SAH or at 6 and 12 months after the first assessment. Predictors of persistent apathy and the impact of apathy on functional outcomes will be examined.Discussion: This will be the first large-scale 1-year follow-up study of apathy in SAH survivors. The findings will provide valuable data to advance our understanding of the clinical course of apathy in this population. Moreover, the results will have clinical relevance by providing essential information to patients, caregivers, and clinicians; promoting the evaluation of apathy; and facilitating the development of prevention strategies, rehabilitation programs, and therapeutic options.